World religions An introduction - Monroe, Charles R. (Amherst Prometheus Books, 1995)
A survey of world religions including prehistoric cosmic religions, Taoism, Hinduism, Zoroastrianism, Judaism, and the branches of Christianity, with particular emphasis on the relationship between Western history and the development of Christian faiths.
Keywords: Religions. Religion -- History. Church history. Religion